Understanding Work Stress and Work-Life Balance among Generation Z Employees in the Modern Workplace - Rifqi Firmansyah Gunawan; Pundani Eki Pratiwi (Nusantara Journal of Behavioral and Social Science, 2026)
The background of this study is based on the increasing importance of work-life balance for generation Z amid increasingly complex work demands that have the potential to cause job stress. This study aims to examine the relationship between job stress and work-life balance among Generation Z employees. The background of this research is based on the increasing importance of work-life balance for Gen Z, alongside the rising demands of modern work environments that may trigger job stress. This study employed a quantitative approach with a correlation survey design involving 218 Gen Z employees years. Data were collected using a job stress scale adapted from Hadiyanti (2025) and a  work-life balance scale adapted from Gunawan et al. (2019). The analysis in this study used Spearman correlation. The results show a significant relationship between job stress and work-life balance (r = 0,695, p < 0,05), indicating a very strong positive correlation. This finding indicates a significant positive association between work stress and work-life balance among Gen Z employees. However, the findings should be interpreted cautiously because the study did not directly assess whether the observed work stress reflects eustress or distress.   Abstrak: Latar belakang penelitian ini didasarkan pada meningkatnya pentingnya work-life balance bagi generasi Z di tengah tuntutan kerja yang semakin kompleks dan berpotensi menimbulkan stress kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara stres kerja dan work-life balance pada karyawan Generasi Z. Latar belakang penelitian ini didasarkan pada meningkatnya pentingnya work-life balance bagi generasi Z di Tengah tuntutan kerja yang semakin kompleks dan berpotensi menimbulkan stres kerja. Penelitian ini menggunakan metode pendekatan kuantitatif dengan desain survei korelasional yang melibatkan 218 karyawan generasi Z berusia 18-28 tahun. Pengumpulan data dilakukan menggunakan skala stress kerja yang diadaptasi Hadiyanti (2025) serta skala work-life balance yang diadaptasi dari Gunawan et al. (2019). Analisa dalam penelitian ini menggunakan korelasi Spearman. Hasil penelitian ini menunjukkan adanya hubungan yang signifikan antara stress kerja dan work-life balance (r = 0,695 ; p < 0,05) dengan kekuatan hubungan yang sangat kuat dan arah positif. Temuan ini menunjukkan adanya hubungan positif yang signifikan antara stres kerja dan work-life balance pada karyawan Gen Z. Namun, temuan tersebut perlu diinterpretasikan secara hati-hati karena penelitian ini tidak secara langsung mengukur apakah stres kerja yang diamati merefleksikan eustress atau distress.